2022
DOI: 10.1016/j.cmet.2021.12.007
|View full text |Cite
|
Sign up to set email alerts
|

STING orchestrates the crosstalk between polyunsaturated fatty acid metabolism and inflammatory responses

Abstract: Summary Concerted alteration of immune and metabolic homeostasis underlies several inflammation-related pathologies, ranging from metabolic syndrome to infectious diseases. Here, we explored the coordination of nucleic acid-dependent inflammatory responses and metabolic homeostasis. We reveal that the STING (stimulator of interferon genes) protein regulates metabolic homeostasis through inhibition of the fatty acid desaturase 2 (FADS2) rate-limiting enzyme in polyunsaturated fatty acid (PUFA) desatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 71 publications
4
60
2
Order By: Relevance
“…It is a regulatory node in cholesterol biosynthesis, and may promote cell proliferation [ 41 ]. FADS2 (fatty acid desaturase 2) may be involved in the coordination of inflammatory responses and metabolic homeostasis [ 42 ]. LSS (lanosterol synthase) catalyzes the conversion of (S)-2,3 oxidosqualene to lanosterol and catalyzes the first step in the biosynthesis of cholesterol, and may play a protective role in the early stages of oxidative stress [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a regulatory node in cholesterol biosynthesis, and may promote cell proliferation [ 41 ]. FADS2 (fatty acid desaturase 2) may be involved in the coordination of inflammatory responses and metabolic homeostasis [ 42 ]. LSS (lanosterol synthase) catalyzes the conversion of (S)-2,3 oxidosqualene to lanosterol and catalyzes the first step in the biosynthesis of cholesterol, and may play a protective role in the early stages of oxidative stress [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 57 ] Moreover, a recent study showed that PUFA (polyunsaturated fatty acid) can inhibit STING. [ 58 ] Collectively, these studies revealed the link between fatty acid metabolism and STING trafficking. Recently, we identified TMEM120A as a positive regulator of STING trafficking from the ER to ERGIC.…”
Section: Tmem120a: a Positive Regulator Of Sting Traffickingmentioning
confidence: 97%
“…This protocol below, used in Vila et al. ( Vila et al., 2022 ) describes the following steps: (i) preparation of dsDNA probes from synthetic ssDNA ( Stetson and Medzhitov, 2006 ), (ii) transfection of dsDNA in murine mouse embryonic fibroblasts (MEFs), and (iii) visualization of the activation of the cGAS-STING pathway by western blot and RT-qPCR. This protocol is the standard protocol used to verify cGAS-STING pathway activation in murine and human cell lines in our laboratory.…”
Section: Before You Beginmentioning
confidence: 99%
“…The protocol can be applied to investigate cGAS-STING signaling in both murine and human cell lines. For complete details on the use and execution of this protocol, please refer to Vila et al. (2022) .…”
mentioning
confidence: 99%
See 1 more Smart Citation